IMPROVING SOPHOMORE LISTENING ABILITY BY USING TOEIC AND TOEFL EXERCISES AT STKIP ABDI PENDIDIKAN PAYAKUMBUH - Mahaputri, Dwi Settya (AT-TALIM, 2013)
The role of listening skills in EFL learning is very crucial not only for academic purpose but also for daily communication.Â  In university level, especially at STKIP Abdi Pendidikan Payakumbuh, students are exposed to listening I until listening III. In academic year 2012-2013, however, students were taught through Test of English as a Foreign Language (TOEFL) and TOEIC to upgrade their critical listening skills. After several treatment or actions, I found out that studentsâ listening skills improved from 61.2 (in the pretest) to 73.5 (post-test).Â  It seemed that both TOEIC and TOEFL exercise have attracted the studentsâ mind that in the second cycle their enthusiasm increased surprisingly.CopyrightÂ Â©Â 2013 by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v20i3.49